Circulating Cell-Free DNA to Determine the Fetal RHD Status in All Three Trimesters of Pregnancy. Issue 6 (December 2016) - Moise, Kenneth J.; Gandhi, Manisha; Boring, Noemi H.; O'Shaughnessy, Richard; Simpson, Lynn L.; Wolfe, Honor M.; Baxter, Jason K.; Polzin, William; Eddleman, Keith A.; Hassan, Sonia S.; Skupski, Daniel W.; Ryan, Greg; et al.
Abstract : OBJECTIVE: To estimate the accuracy of a new assay to determine the fetal RHD status using circulating cell-free DNA. METHODS: This was a prospective, observational study. Maternal blood samples were collected in each trimester of pregnancy in 520 nonalloimmunized RhD-negative patients. Plasma samples were analyzed for circulating cell-free DNA using the SensiGENE RHD test, which used primers for exons 4 and 7 as previously described and incorporated a new primer design for exon 5 of the RHD gene. Neonatal serology for RhD typing using cord blood at birth was undertaken and results were stored in a separate clinical database. After unblinding the data, results of the DNA analysis were compared with the neonatal serology. RESULTS: Inconclusive results secondary to the presence of the RHD pseudogene or an RHD variant were noted in 5.6%, 5.7%, and 6.1% of the first-, second-, and third-trimester samples, respectively. The incidence of false-positive rates for RhD (an RhD-negative fetus with an RHD -positive result) was 1.54% (95% confidence interval [CI] 0.42–5.44%), 1.53% (CI 0.42–5.40%), and 0.82% (CI 0.04–4.50%), respectively. There was only one false-negative diagnosis (an RhD-positive fetus with an RHD -negative result), which occurred in the first trimester (0.32%; 95% CI 0.08–1.78%). Genotyping for mismatches across repeated samples revealed that this error was related to mislabeling of samples from two patients collected on the same day at one of the collection sites. Overall test results were in agreement across all three trimesters ( P >.99). CONCLUSION: Circulating cell-free DNA can accurately predict the fetal RhD status in all three trimesters of pregnancy. Abstract : Maternal circulating cell-free fetal DNA can accurately predict the fetal RHD type in all three trimesters of pregnancy.